Weather analysis and forecasting : applying satellite water vapor imagery and potential vorticity analysis - Santurette, Patrick (Elsevier, 2005)
A practical training manual and guide to analyzing circulation patterns and satellite imagery to improve operational forecasting.
Keywords: Satellite meteorology.; Water vapor, Atmospheric.; Weather forecasting.; Météorologie par satellite.; Vapeur d'eau atmosphérique.; Temps (Météorologie) -- Prévision.; NATURE -- Weather.; SCIENCE -- Earth Sciences -- Meteorology & Climatology.; Satellite meteorology; Water vapor, Atmospheric; Weather forecasting; dissertations.; Academic theses; Academic theses.; Thèses et écrits académiques.